Aerobic exercise has beneficial impact on atherogenic index of plasma in sedentary overweigh and obese women - Stranska, Zuzana; Matoulek, Martin; Vilikus, Zdenek; Svačina, Štěpán; Stránský, Pravoslav (Neuro-endocrinology letters, 2011)
OBJECTIVE: In obese patients, we hypothesized physical exercise (PE) to affect lipids through its intrahepatic fat accumulation-lowering effect, associated with a decrease of total body fat (Fat%) and even weight (Mass). Design and setting: Thirty seven sedentary, non-diabetic women (BMI median 34.8) from our out-patient department were tested. Elimination criteria: recent weight reduction, lipid-influencing or heart rate-modifying medication. Participants: 50 entering, 37 finishing, 7 excluded for processing failure, 6 did not fulfill the protocol. INTERVENTIONS: PE protocol: 60 min supervised trainings, intensity at 65% of VO2max, modified by the clamp heart rate test. Median of total training hours was 34 during 115 days (median). Main Outcome Measurements: an effect of PE on total cholesterol (CH), triglycerides (TG), HDL-cholesterol (HDL_C), LDL-cholesterol (LDL_C), index of atherogenity (IA), atherogenic index of plasma (AIP), maximum peak oxygen consumption (VO2max), Mass, body mass index (BMI), waist circumference (Waist) and Fat%. RESULTS: Statistically significant differences at start (_s) and the end (_e) of PE (p<0.05): AIP -0.049, Mass -3.6 (kg), BMI -1.7 (kg/m2), Waist -2.5 (cm), Fat% -2.5, VO2max 2.92 (L.min-1kg-1). Correlation coefficients, Pearson's between Gaussian distributed (Gd-v) variables and Spearman ́s (non Gd-v) statistically significant (p<0.05): IA and BMI, IA and Mass, IA and Waist, IA and Fat%, LDL and BMI, LDL and Mass, LDL and Fat%, LDL and Waist, IA and VO2max, LDL_C and VO2max. CONCLUSIONS: PE improves lipid profile towards production of antiatherogenic particles more likely due to changes in anthropometric parameters than in improvement of physical fitness.
Keywords: dospělí; sedavý životní styl; index tělesné hmotnosti; Humans; Atherosclerosis; Obesity; lidé středního věku; Middle Aged; Exercise; spotřeba kyslíku; Body Mass Index; Cholesterol, HDL; Physical Fitness; Adult; cvičení; Oxygen Consumption; Triglycerides; Sedentary Behavior; ženské pohlaví; Female; LDL-cholesterol; lidé; HDL-cholesterol; ateroskleróza; tělesná výkonnost; obezita; Cholesterol, LDL; triglyceridy